Cyberbullying Among Middle Schoolers : Focusing in on the Causes and Consequences. - Lippman, Trevor (My University, 2009)
Although there has been ample research on traditional forms of bullying, little research has been done addressing cyberbullying. This study attempts to discover what school climate factors may lead to cyberbullying behaviors. If certain school characteristics can be discovered that make a juvenile more prone to cyberbullying behaviors, school policies can be put into place to reduce the amount of cyberbullying going on in and out of the school setting.
Color poster with text, images, and tables describing research conducted by Trevor Lippman, advised by Justin W. Patchin.
Keywords: Cyberbullying; Bullying in schools; School environment--Social aspects; Middle school students; Posters